1993
DOI: 10.1073/pnas.90.7.2989
|View full text |Cite
|
Sign up to set email alerts
|

Functional inhibition of retinoic acid response by dominant negative retinoic acid receptor mutants.

Abstract: The diverse effects of retinoids on the development, growth, and homeostasis of vertebrate organisms are mediated in part by three distinct isoforms of retinoic acid receptors (RARs). These proteins, which are structurally and functionally closely related to thyroid hormone receptors and the oncogene product v-ErbA, regulate patterns of gene expression in target tissues. One approach to study the distinct effects of retinoic acid in cells is to subvert this activity of endogenous receptors by expression of dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
147
0
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(155 citation statements)
references
References 37 publications
7
147
0
1
Order By: Relevance
“…Transgenic and knockout mice studies have shown that these genes are important for facial development [36,37]. Various human studies have reported both positive and negative results near the RARA gene.…”
Section: Q12-q21 (Rara Clf1)mentioning
confidence: 99%
“…Transgenic and knockout mice studies have shown that these genes are important for facial development [36,37]. Various human studies have reported both positive and negative results near the RARA gene.…”
Section: Q12-q21 (Rara Clf1)mentioning
confidence: 99%
“…Our results also support the concept that some of the biological effects of RA and 9-cis RA might be mediated solely by RXRs acting as hormone receptors. This is particularly interesting in view of the tissue-specific and developmental regulation of multiple RXR subtypes (17,26,43,56,59) and the recently discovered phenotypic similarities between mice lacking RXRot and those with congenital vitamin A deficiency (57).…”
mentioning
confidence: 99%
“…However, introducing a normal RARā£ cDNA into these cells restores their differentiating response to . Both the ligand-dependent transcriptional activation function AF-2 (located in the RARā£ E region) and the ligand-independent transcriptional activation function AF-1 (located in the RARā£ A/B region) are involved in cell differentiation (33,34). In vitro studies show that CAK phosphorylates RARā£ at both the A/B and F regions (23).…”
mentioning
confidence: 99%